Short-term effect of native and bioprocessed food residues on the suppression of root-knot Meloidogyne incognita in tomato plants - Claudio Cacace; Trifone D’Addabbo; Michela Verni; Carlo Giuseppe Rizzello; Matteo Spagnuolo; Gennaro Brunetti; Pasqua Veronico; Francesco De Mastro; Andreina Traversa; Claudio Cocozza (Frontiers in Sustainable Food Systems)
IntroductionEnsuring crop health is essential to meet the growing demand for food and effectively managing root-knot nematodes (RKNs) can help maximize agricultural output. Indeed, plant diseases caused by RKNs belonging to the genus Meloidogyne, among the most harmful pests of horticultural crops, lead to severe productivity and economic losses.MethodsThis study aimed at assessing the effectiveness of wasted bread, brewers’ spent grain, and spent coffee grounds, native or bioprocessed, to suppress RKN Meloidogyne incognita, when used as soil amendments. Bioprocessing included the use of enzymatic treatments and fermentation with selected lactic acid bacteria or an incubation with compost tea. The matrices were incorporated to infested soil at doses corresponding to 3,000 kg ha−1 organic carbon. Biomasses were characterized for their main physico-chemical and biochemical properties. Then plant growth and soil infestation were monitored to assess the biomasses potential as amendments.ResultsThe different nature of the biomasses resulted in a supplementation in total nitrogen, phosphorous, organic acids and phenolic compounds strictly dependent on the food residue used and the bioprocessing employed. Although all the amendments significantly suppressed the multiplication of M. incognita and gall formation on tomato roots (up to 98 and 79%, respectively), the strongest suppressive effect was achieved by using bioprocessed brewers’ spent grain, resulting in performances comparable to synthetic nematicides (79 eggs and juveniles g−1 roots).DiscussionThe nematocidal effect was ascribed to phenolic compounds and organic acids produced during lactic acid bacteria fermentation. Bioprocessed brewers’ spent grain also resulted in the best growth effect on tomato plants.